Neonatal sepsis by gram negative bacteria and antibiotics susceptibility pattern at a tertiary care Paediatric Hospital in Pakistan - Javed, Shamsa; Mehdi, Naima; Majeed, Nadia; Tahir, Anum; Mir, Nazia Akber; Javed, Humera (Infectious Diseases Journal of Pakistan, 2024)
Background: Neonatal sepsis has become a leading contributor to mortality and morbidity among neonates in developing countries with recent surge in infections with multidrug resistant Gram-negative bacteria. Aim of this study was to find out the spectrum of Gram-negative organisms and their antimicrobial susceptibility pattern in neonatal sepsis. Material and Methods: This is a cross-sectional study conducted in the Department of Microbiology, University of Child Health Sciences, The Children’s Hospital, Lahore from September to December 2023. A total of 374 blood culture samples received from neonatal unit were incubated at 37 °C for upto 7 days and sub cultured on blood and MacConkey agar after observing signs of growth. Bacterial isolates were identified by standard microbiological techniques. Antimicrobial testing was done by Kirby-Bauer disc diffusion method. Data was analyzed with descriptive statistics using SPSS 23.0. Results: Out of 374 neonates, males were predominant (n=238, 63.6%). Eighty-seven (23.3%) cultures were positive for Gram negative bacilli which comprised of 29.9% Klebsiella pneumoniae, 23% Acinetobacter baumannii, 17.2% Enterobacter spp., 8.1% Serratia marcescens, 10.4% Pseudomonas spp., 4.6% Escherichia coli, 3.4% Pantoea spp., 2.3% Burkholderia cepacia and 1.1% Stenotrophomonas maltophilia. High resistance to multiple groups of antibiotics including β-lactams, β-lactam combinations, cephalosporins and aminoglycosides was observed among majority of the isolates. Conclusion: In this study, Klebsiella pneumoniae were the most common isolates in neonatal sepsis. High antibiotics resistance is an alarming situation. Antimicrobial stewardship is required to develop appropriate guidelines for empiric antimicrobial use. Keywords: Neonatal sepsis, Gram negative bacteria, Antimicrobial resistance, Antimicrobial stewardship